Mercapto functionalized sepiolite: a novel and efficient immobilization agent for cadmium polluted soil. Issue 63 (16th August 2017) - Liang, Xuefeng; Qin, Xu; Huang, Qingqing; Huang, Rong; Yin, Xiuling; Wang, Lin; Sun, Yuebing; Xu, Yingming
Abstract : Mercapto functionalized sepiolite (MSEP) as a novel and efficient immobilization agent could reduce the accumulation of Cd in husked rice ( Oryza sativa L.) by 65.4–77.9% at trace dosages of 0.1–0.3%. Abstract : Immobilization agents are the key factor that determine the success of immobilization remediation in heavy metal polluted soil. In this study, mercapto functionalized sepiolite (MSEP) as a novel and efficient immobilization agent was prepared through surface modification and utilized for the remediation of cadmium (Cd)-polluted paddy soil in pot trials. MSEP at trace dosages of 0.1–0.3% could reduce the Cd content of husked rice ( Oryza sativa L.) by 65.4–77.9%; this was more efficient than the traditional pH regulating amendments such as clay minerals. Single and sequential procedures demonstrated that MSEP could enhance the fixation or sorption of Cd on soil compositions and reduce the bioavailability of Cd. MSEP had negligible effects on the pH values and the point of zero charge (PZC) of paddy soil, and had no obvious impact on extractable zinc, hydrolyzable nitrogen and available phosphorus in the soil, indicating that it is environmental friendly and compatible. Physiologically, MSEP could increase total antioxidant capacity (T-AOC) and nonprotein thiol (NPT) content and reduce the malondialdehyde (MDA) content of rice root so that MSEP could alleviate the stress of Cd in rice. In general, compared to natural sepiolite as a traditional pH-regulating amendment in the present study, the primary immobilization mechanism and environmental compatibility and friendliness of MSEP are its great advantages. The trace application dosages could save economic costs and facilitate easier large-area application. Thus, we recommend MSEP as a novel and efficient immobilization agent for the remediation for Cd-polluted paddy soil.